2020
DOI: 10.7150/jca.45077
|View full text |Cite
|
Sign up to set email alerts
|

Circulating let-7f-5p improve risk prediction of prostate cancer in patients with benign prostatic hyperplasia

Abstract: Background: Although the prostate-specific antigen (PSA) testing was widely used for early detection of prostate cancer (PCa), it is difficult for PSA to distinguish the PCa from benign prostatic hyperplasia (BPH) patients. Emerging evidence has shown that microRNA (miRNA) was a promising biomarker for PCa screening. Methods: We applied miRNA profiling from microarray or high-throughput sequencing in Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) databases to identify the differentially expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…let-7f-5p is indispensable for various physiological and biological processes, including cell differentiation ( Wu et al., 2007 ), immune response ( Sathe et al., 2014 ), and angiogenesis ( Nicoloso and Calin, 2008 ). A previous study implicates elevated let-7f-5p expression as a biomarker for multiple malignant diseases, including non-muscle-invasive bladder ( Shee et al., 2020 ) and prostate cancers ( Ge et al., 2020 ). miR-222a, a miR-221/222 cluster component ( Chun-Zhi et al., 2010 ), is aberrantly expressed in hepatocellular carcinoma ( Wang et al., 2019 ), epithelial tumors ( Gaetani et al., 2020 ), and virus-infected cells ( Zhao et al., 2019 ; Song et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…let-7f-5p is indispensable for various physiological and biological processes, including cell differentiation ( Wu et al., 2007 ), immune response ( Sathe et al., 2014 ), and angiogenesis ( Nicoloso and Calin, 2008 ). A previous study implicates elevated let-7f-5p expression as a biomarker for multiple malignant diseases, including non-muscle-invasive bladder ( Shee et al., 2020 ) and prostate cancers ( Ge et al., 2020 ). miR-222a, a miR-221/222 cluster component ( Chun-Zhi et al., 2010 ), is aberrantly expressed in hepatocellular carcinoma ( Wang et al., 2019 ), epithelial tumors ( Gaetani et al., 2020 ), and virus-infected cells ( Zhao et al., 2019 ; Song et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the diagnostic potential of microRNA-34a and microRNA-31 is analogous to combined microRNA panels for the early diagnosis of EOC. Recent study showed combined diagnostic value of miR-34a and CA-125 could discriminate EOC from normal with an AUC of 0.818, while lower expression of let-7f has the diagnostic value of AUC 0.78 [ 24 29 30 31 32 ]. Moreover, the comparative expression analysis of let-7f in different cancers (colorectal, lung, prostate, papillary thyroid cancer) showed a higher diagnostic value for discriminating respective cancer from the normal [ 29 31 32 33 34 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent study showed combined diagnostic value of miR-34a and CA-125 could discriminate EOC from normal with an AUC of 0.818, while lower expression of let-7f has the diagnostic value of AUC 0.78 [ 24 29 30 31 32 ]. Moreover, the comparative expression analysis of let-7f in different cancers (colorectal, lung, prostate, papillary thyroid cancer) showed a higher diagnostic value for discriminating respective cancer from the normal [ 29 31 32 33 34 35 ]. Very few reports are available on exploring the diagnostic value of these selected microRNA in EOC; therefore, the discriminative potential of each microRNA and integrated microRNA panel from the present study could aid in predicting early-stage ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, immunotherapy, especially adoptive immunotherapy, has shown great benefits for patients with advanced prostate cancer. Recent research showed that plasma let-7f-5p combined with a prostate-specific antigen is used as a biomarker for the diagnosis of prostate cancer [ 109 , 110 ]. The F-actin-binding protein switch-associated protein 70 (SWAP70, SWAP switch B cell complex 70 kDa subunit) is involved in the activation of B cell transformation.…”
Section: Different Cancers and Related Abpsmentioning
confidence: 99%